Differential expression of catalase genes in Nicotiana plumbaginifolia (L.). - Willekens, H (1994)
We have analyzed the expression of three catalase (Cat; EC 1.11.1.6) genes from Nicotiana plumbaginifolia by means of RNA blot and in situ hybridizations. Our data demonstrate that the expression of each catalase is associated with a particular H2O2-producing process. Cat1 appears to be specifically involved in the scavenging of photorespiratory H2O2 and is under control of a circadian rhythm, Cat2 is uniformly expressed in different organs with a cellular preference for vascular tissues, and the expression profile of Cat3 points to a role in glyoxysomal processes. Differential expression of these catalases is also manifested in response to temperature changes. DNA sequence comparison with other dicotyledonous catalases led to the identification of at least three distinct classes, which indicates that the functional organization of catalases is generally conserved in dicotyledonous plants.